INNOVATION IN THE DEVELOPMENT OF STTAL HUMAN RESOURCES TO FACE THE 4.0 INDUSTRIAL REVOLUTION - Risa Apriyani; Avando Bastari; Mukhlis Mukhlis (JOURNAL ASRO, 2019)
In the era of the Industrial Revolution 4.0. this is where technology and technology have been very advanced demanding competent human resources who have high morale and discipline in carrying out their roles and functions for both the individual and the objectives of the organization. In the role and contribution of STTAL in the Industrial Revolution 4.0, the current conditions, where the quality of human resources both students, lecturers, and Antap STTAL are considered unable to answer the challenges in the cyber field so that strategic decision-making and steps are needed to be able to accompany the development of science and technology while carrying out missions STTAL is to hold a higher education program to produce human resources with Indonesian character and personality, quality and relevant science and technology based, with defense needs in the military, maritime and maritime fields. With SWOT analysis, a matrix will be obtained which shows the strengths and weaknesses as well as opportunities and threats which will later be used as a reference to make the right and appropriate strategies. Keywords: SWOT Analysis, STTAL HR Quality, Industrial Revolution 4.0